26=u-17

Simple and best practice solution for 26=u-17 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 26=u-17 equation:


Simplifying
26 = u + -17

Reorder the terms:
26 = -17 + u

Solving
26 = -17 + u

Solving for variable 'u'.

Move all terms containing u to the left, all other terms to the right.

Add '-1u' to each side of the equation.
26 + -1u = -17 + u + -1u

Combine like terms: u + -1u = 0
26 + -1u = -17 + 0
26 + -1u = -17

Add '-26' to each side of the equation.
26 + -26 + -1u = -17 + -26

Combine like terms: 26 + -26 = 0
0 + -1u = -17 + -26
-1u = -17 + -26

Combine like terms: -17 + -26 = -43
-1u = -43

Divide each side by '-1'.
u = 43

Simplifying
u = 43

See similar equations:

| 45-3x=9-9x | | 46-j=31 | | 4x^2-20x+26=1 | | 84=x+0.2x | | 60=69-f | | 18x+14x-27y= | | 3=89-g | | 52-q=32 | | 10+12x=-56+x | | n-57=19 | | h-49=0 | | 4+3n=5(2-2n) | | 16=s-50 | | 29=q-51 | | 3a+5b=15 | | 8k+5k-10k= | | 56-d=27 | | 2+2u+7=42 | | w-10=58 | | 6=k-15 | | 4=m-63 | | 7x-3=x+7 | | 12-(3x-6)-5(7-x)= | | 39-w=2 | | y-65=9 | | (4t+9)-(-2+7)=0 | | A=p+pnr | | p-10=25 | | 8=n-65 | | 52q=32 | | b^4-ab^3+b^2c=0 | | 7*cos^2*x-cos*x-8=0 |

Equations solver categories